ChemInform Abstract: Crystal Structure of Tris(ethylenediammonium) Hexasulfatopraseodymium(III) Hexahydrate. Issue 47 (6th November 2014) - Held, Peter
Abstract (H2en)3 [Pr2(SO4)6]·6H2O is obtained from a 1:1:2 molar aq.